Features of Phonemic Theory in the Arabic Heritage and Its Role in Building Modern Phonological Study - zellagui, houria (El Omda in Linguistics and Discourse Analysis, 2018)
Many topics in modern phonetic study have their roots in the classical linguistic heritage, particularly in Arabic phonetic tradition, especially in the field of phonology, despite the claims of many linguists that they are achievements of modern phonetics. Undoubtedly, the aspiration to create a bridge connecting Arabic and foreign linguistic studies continuously, in light of the rapid scientific development of the latter, makes it essential to explore, utilize, and invest in these materials. This is necessary to develop the field, solve its problems, eliminate the causes of its obstacles, and unlock the barriers that hinder any attempt to advance it. Hence, the importance of integrating it into the scientific research system, by reinterpreting it according to the needs of the era and its constantly evolving requirements.